O papel do indivíduo na evolução institucional de Veblen - Moura, Ana Carolina (2017)
According to Veblen (1915), the evolution of institutions is the same as institutional development and this is the development of society. The aim of this paper is answer the question: what is the role of the individual in Veblen's institutional evolution? The general objective is to seek the role occupied by the individual in Veblen's institutional evolution. In order to achieve the general objective, we developed an analytical framework that presents the fundamental characteristics of the Evolutionary Economic Theory. The specific objective is investigate the fundamental characteristics of an Evolutionary Economic Theory and a form of presentation as an analytical framework that is to evaluate a Veblen’s Theory and the role of the individual in it. To understand what the fundamental elements of an Evolutionary Economic Theory are it is necessary to clarify what an evolutionary ontology is. According to Dopfer and Potts (2008, 2004), an ontology serves as a foundation for an Evolutionary Economic Theory and is made up of scientific claims about a fundamental nature of reality. As an alternative to evolutionary ontology, Dopfer and Potts (2008; 2004) propose the Evolutionary Realism. After defining the evolutionary ontology, we starts with the construction of the fundamental characteristics of Evolutionary Economic Theory that are in conformity with Evolutionary Realism. In order to do that we use the works of Witt (2014), Metcalfe (1998), Lawson (2003) and Potts (2003). From the union these four authors combined with an evolutionary ontological orientation, we concluded that four elements fundamental to an Evolutionary Economic Theory are variation, selection, replication and adaptation. These elements are fundamental characteristics of the Evolutionary Economic Theory and connect in the analysis framework through the Witt’s (2014) modalities. To begin this evaluation it is necessary to clarify who the population and the unit of selection are. This structure is a tool for analysis the evolutionary theory of Veblen. This method of evaluating the individual's role applied in a selection of Veblen's writings leads to the conclusion that through his instincts, habits, and institutions, the Veblen’s individual has characteristics of variation, selection, adaptation and replication. In institutional evolution, it has a multiple role, sometimes acting as an agent through its instincts and habits, or else it takes a more passive stance, where it is shaped by the institutional environment. The multiple role of the individual in Veblen can be conceived scientifically and theoretically, when we incorporates in the theoretical structure the explanation of type (iii). This kind of explanation makes it possible to conceive the history of adaptive processes that are also interactive in which selection, adaptation and replication are imperfect, opening the way for the generation of new variation. An evolutionary ontology allows creating scientific theories in these molds.